'He knows he is safe; you are the safety net'. Key adult intervention with children with attachment difficulties: the TAs perspective. Issue 1 (5th February 2023) - Blackwood, Lisa; Farrow, Brenna
Abstract : Children and young adults who are 'looked after' can present teachers and teaching assistants with a variety of day‐to‐day classroom challenges and a range of complex behaviours due to adverse childhood environments. This group of vulnerable young people have very complex social and emotional behaviours that require a considered approach of support and interventions. The types of interventions deployed in schools, however, may depend on staff knowledge, staff self‐confidence, and interpersonal skills to support the child's learning and complex behaviours. An example of an intervention is the key adult intervention programme, which is purported to develop staff knowledge and self‐confidence when working with looked after children. training in key adult intervention occurred at a special school, which had a high percentage of looked after children, situated in an East Midlands town. The purpose of the study was firstly to support the children through in‐depth knowledge development for supporting staff, and secondly to investigate staff confidence and understanding of the needs of looked after children. In addition, supporting factors of the key adult intervention and a discovery of any barriers to its implementation were sought. Using a mixed methods approach, data were collected from participating staff using questionnaires and focused conversations. Qualitative data were analysed using Cresswells six‐step process. Findings suggest that the key adult intervention is an effective means to support staff confidence and understanding and offer support for looked after children. Recommendations for future practice include increased training and support for teaching assistants, teachers and the school community as a whole. In addition, targeted professional and emotional support for the teaching assistants deployed, and increased communication between senior leaders and teaching assistants is crucial. The current research, therefore, adds to existing literature by providing an evaluation of the key adult intervention within a special school setting with evidence gathered from teaching assistants.